Diagnosis and Management of Trigeminal Neuralgia in Dentistry: A Literature Review - Halim, Susanna; Sania, Nadia Putri (Pascasarjana, Mataram University, 2025)
Trigeminal neuralgia (TN) is a paroxysmal neuropathic pain disorder characterized by sharp, brief, and recurrent pain in the trigeminal nerve distribution. Because it occurs in the maxillofacial region, TN is frequently mistaken for odontogenic pain, leading patients to seek dental care and risk unnecessary procedures. This review aims to summarize current literature on the clinical features, diagnostic challenges and management of trigeminal neuralgia in dental practice, highlighting the important role of dentist in its detectione and care. The diagnosis of trigeminal neuralgia was based on multidisciplinary approach, including history taking according to ICHD-3 criteria, dental vitality testing, neurological examination and MRI, with specialist collaboration in complex cases. The results showed that trigeminal neuralgia is frequently misdiagnosed as odontogenic pain, requiring history, neurological exam, MRI, and dental evaluation for accurate diagnosis. Carbamazepine was the primary treatment, with surgery for refractory cases, and a multidisciplinary approach proved essential. Trigeminal neuralgia requires accurate evaluation and dentist involvement to ensure proper diagnosis and effective management.